Association of Cytochrome P450 2A6 (CYP2A6) Gene Polymorphisms with Fatty Acid Traits in Indonesian Native Sheep - Gilang Kurnia Abdillah; Kasita Listyarini; Ratna Sholatia Harahap; Asep Gunawan; Cece Sumantri (Faculty of Animal Science, Universitas Gadjah Mada, 2021)
A member of the cytochrome P450 superfamily enzyme that play a role in microsomal fatty acids oxidation process encoded by cytochrome P450 2A6 (CYP2A6). This study aimed to examined the CYP2A6 gene polymorphisms and their association on fatty acid traits in Indonesian native sheep. A total of 299 rams aged 10-12 months with body weights between 20-30 kg used to identify the CYP2A6 gene polymorphism are consisted of 36 samples of barbados cross sheep (BCS), 35 samples of compass agrinak sheep (CAS), 20 samples of javanese fat tailed sheep (JFT), 36 javanese thin tailed sheep (JTT), 20 samples of garut sheep (GS), 45 samples of garut composite sheep (GCS), meanwhile for the fatty acid analysis was carried out by using 107 of loin samples from the total sheep. Identification of the CYP2A6 gene polymorphisms were performed using PCR-RFLP (Polymorphism Chain Reaction-Restriction Fragment Length Polymorphism) with the BSmAI restriction enzymes. The amplification product was 286 bp. Polymorphism were found in JFT, JTT, GCS and JS with GG and GT genotypes, while BCS, CAS, and GS were monomorphic with TT genotype. The CYP2A6 BSmAI polymorphism was in Hardy-Weinberg Equilibrium for JFT, JTT and JS, while BCS, CAS, GS, GCS, and combined was deviated based on chi square. A SNP g.49170107 G>T of the CYP2A6 gene polymorphism was significantly associated (P <0.05) with only erucic acid (C22:1n9). The GT genotypes had a higher value than GG genotypes The CYP2A6 gene could be used as a selection marker to improve fatty acid traits in Indonesian native sheep.